Model Produktivitas Usahatani Padi Ciherang Di Desa Hambuku Hulu Kecamatan Sungai Pandan Kabupaten Hulu Sungai Utara - Azwar Saihani; Erni Mustika Erni Mustika (Rawa Sains: Jurnal Sains STIPER Amuntai, 2014)
This study aims to determine the influence of these factors on the productivity of farm productivity in Rice Ciherang The Hambuku Hulu Village Sungai Pandan District, to determine what factors significantly affect the productivity of Rice Ciherang farming in the Hambuku Hulu Village Sungai Pandan District and to how farm productivity of Rice Ciherang in the Hambuku Hulu Village Sungai Pandan District. The research was conducted in the village of Upper Hambuku Hulu Vilage Sungai Pandan District. Methods of data collection is done by survey and interview methods. The number of farmers respondent taken in this study is 52 peoples. Factors tested were considered to affect the productivity of rice farming is a factor Ciherang land, seeds, fertilizers and pesticides. The results showed that calculated F value contained in the Anova table is equal to 4,032 with significant value of 0,007, so the significant value of 0,007 < 0,05 so H0 is rejected and Ha is accepted, it means the factors that are considered are the factors affecting land, seeds, fertilizers and pesticides simultaneous significant effect on the productivity of Rice farming Ciherang. Adjusted R2 value of 0,192 indicates that the influence of land, seeds, fertilizers and pesticides to the rice farm productivity Ciherang amounted to 19,2 % and 80,8 % influenced by other factors not included in the regression of capital. The test results of regression coefficients showed that partial factors that have a real impact on the productivity of rice farming is a factor Ciherang fertilizer while the factors of land, seeds and pesticides are not a real effect on the productivity of rice farming Ciherang. The average productivity of Rice Ciherang farming in the Hambuku Hulu Village is 46,74 Kw/ha can be said to be good with an average production of 80,06 Kw and the average land area of 1,68 Ha.